Islamic Worldview and Mental Health Strengthening in Islamic Educational Tradition - M. Ardiansyah; Muhammad Jamaluddin; Kholili Hasib (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2026)
Mental health challenges in educational contexts require culturally sensitive interventions that align with students’ worldviews and religious values. This library research examines the relationship between Islamic worldview and mental health strengthening within Islamic educational traditions. The study employed systematic literature review methodology, analyzing peer-reviewed articles from multiple databases including PubMed, PsycINFO, and Scopus, focusing on publications from 2018-2025. Thematic analysis identified key concepts regarding Islamic worldview’s role in promoting psychological wellbeing. Results reveal three main findings: First, Islamic worldview provides robust conceptual foundations for mental health through principles of balance (mīzān), trust in Allah (tawakkul), patience (sabr), and community support (ummah). Second, Islamic educational institutions implement comprehensive mechanisms including integrated spiritual-academic programs, mentorship systems, communal learning approaches, therapeutic practices, and supportive physical environments. Third, contemporary research demonstrates significant effectiveness of Islamic worldview-based approaches in addressing culture-specific mental health challenges, with evidence showing improved treatment adherence, enhanced coping abilities, and better psychological outcomes compared to conventional interventions. The study concludes that Islamic worldview offers valuable contributions to global mental health practice through holistic frameworks that integrate spiritual, psychological, and social dimensions, providing culturally authentic and therapeutically effective approaches for Muslim students in educational contexts.